2014
DOI: 10.1016/j.alcohol.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol exposure during adolescence or in adulthood on Pavlovian conditioned approach in Sprague-Dawley rats

Abstract: Human studies have shown that adolescents who repeatedly use alcohol are more likely to be dependent on alcohol and are more likely to suffer from psychological problems later in life. There has been limited research examining how ethanol exposure in adolescence might contribute to later abuse or addiction in adulthood. The present experiment examined effects of intermittent ethanol exposure during adolescence on sign-tracking behavior in adulthood, indexed by a Pavlovian conditioned approach (PCA) task wherei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 51 publications
4
41
7
Order By: Relevance
“…Here we demonstrate that adolescent alcohol exposure shifts the normal distribution of conditioned responses elicited by Pavlovian cues exclusively toward a sign-tracking phenotype. These data are in support of a previous study which reported that alcohol exposure during adolescence, but not during adulthood, increased sign-tracking behavior in rats (McClory and Spear, 2014). Indeed, the sign-tracking phenotype has been specifically linked to models of AUD (Tomie and Sharma, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Here we demonstrate that adolescent alcohol exposure shifts the normal distribution of conditioned responses elicited by Pavlovian cues exclusively toward a sign-tracking phenotype. These data are in support of a previous study which reported that alcohol exposure during adolescence, but not during adulthood, increased sign-tracking behavior in rats (McClory and Spear, 2014). Indeed, the sign-tracking phenotype has been specifically linked to models of AUD (Tomie and Sharma, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…This would suggest that singly housing animals in the current work did not shift the overall distribution of response biases and is therefore not the likely explanation for the extreme shift in the alcohol group exclusively to sign-tracking behavior. Importantly, a previous study in which rats were pair-housed and exposed to intragastric alcohol or control administration during adolescence observed that alcohol-treated animals showed increased lever-pressing behavior during Pavlovian conditioning consistent with the results outlined here (McClory and Spear, 2014), indicating that the effects of alcohol on learning are consistent across housing conditions. Finally, our work demonstrating that adolescent alcohol promotes maladaptive decision making (Nasrallah et al, 2011;Schindler et al, 2014), findings that we have previously linked to learning effects similar to the ones found here (Clark et al, 2012), have been replicated in animals that were group housed during intragastric alcohol administration in adolescence (Boutros et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Given that bLRs and bHRs are known to differ in these behaviors, the effects of adolescent cocaine treatment on Pavlovian conditioned approach behavior were analyzed separately within each phenotype. Contrary to what we initially hypothesized based, in part, on previous findings (Doremus-Fitzwater and Spear 2011; McClory and Spear 2014; Saddoris et al 2016), bLR rats exposed to cocaine during adolescence did not acquire a sign-tracking response as measured by the number of lever-CS contacts, probability to approach the lever-CS, and latency to contact the lever-CS (Fig. 4 a–c).…”
Section: Resultscontrasting
confidence: 96%
“…Previous studies in outbred rats have shown that exposure to ethanol during adolescence (McClory and Spear 2014) increases sign-tracking behavior, as does exposure to psychostimulants either during adolescence (Doremus-Fitzwater and Spear 2011) or in adulthood (Saddoris et al 2016). While the specific neurobiological mechanisms underlying these drug-induced effects on sign-tracking behavior have not been elucidated, dopaminergic transmission in the NAc core is likely involved (Saddoris et al, 2016), as it has been shown to play a critical role in the sign-tracking, but not the goal-tracking response (Flagel et al 2011; Saunders and Robinson 2012; Yager et al 2014).…”
Section: Introductionmentioning
confidence: 99%